Resistivity, I–V characteristics and Hall effect in Dy0.5(Sr1-xCax)0.5MnO3 manganites. (November 2017) - Hamdi, R.; Tozri, A.; Smari, M.; Dhahri, E.; Bessais, L.
Graphical abstract: Highlights: The resistivity of Dy0.5 (Sr1-x Cax )0.5 MnO3 (x = 0 and x = 0.3) systems showed that these samples exhibited an insulating behavior. I–V characteristics of both samples deviate from the Ohmic behavior. Magnetoresistance and electroresistance provided negative values. Hall resistivity ρxy of the Dy0.5 Sr0.5 MnO3 sample presents electron-like type of the charge carriers. The temperature coefficient of resistance (TCR) shows that both systems can be good candidates for bolometer applications. Abstract: Dy0.5 (Sr1-x Cax )0.5 MnO3 (x = 0 and x = 0.3) manganites were synthesized using sol-gel method. Both samples exhibited an insulating behavior in the whole temperature range. Even the application of 5 T magnetic fields does not change this state. Conduction mechanisms were also investigated. The I–V characteristics of both samples present Ohmic behavior at minor voltages. Magnetoresistance and electroresistance were also studied. The thermal variation of Hall resistivity of Dy0.5 Sr0.5 MnO3 was determined in cooling down and warming up processes revealing electron-like type of charge carriers. Temperature coefficient of resistance shows significant values for both systems making them good candidates for bolometer applications.